Low-noise electronic system design - Motchenbacher, C. D. (John Wiley and Sons, 1993)
Emphasizes IC design concepts with additional support for discrete design where necessary. Describes noise sources and models; addresses practical problems of circuit design for low noise using negative feedback, filtering, component noise, measurement techniques and instrumentation; gives numerous examples of practical amplifier designs. Five chapters cover the use of SPICE and PSpice for low noise analysis and design.